Tuberculous Abscess of the Anterior Abdominal Wall: An Unusual Site of Presentation - Awad Ali M Alawad; Mohamed D Gismalla (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2015)
The skeletal muscles are rarely affected by tuberculosis because they are not a favorable site for the survival and multiplication of Mycobacterium tuberculosis. A case of tuberculous abscess in rectus abdominis muscle is described in a 20- year- old female in an apparently healthy individual without any past history of tuberculosis. The diagnosis was made by ultrasound-guided fine-needle aspiration and cytological examination which revealed caseating granuloma with central necrosis, lymphocytes, and giant cells, consistent with tuberculosis. After four weeks' antituberculous treatment, she responded well and the abscess regressed considerably. In most cases, the muscle involvement is secondary and is caused by either hematogenous route or direct inoculation from a tuberculous abdominal lymph node or extension from underlying tubercular synovitis and osteomyelitis. This case cautions the clinicians and radiologists about the possibility of tuberculosis in considering the differential diagnosis of any lesion even in any unlikely anatomical area, especially in those areas where tuberculosis is endemic.